O ensino de parte da geometria do ensino fundamental: análise de dificuldades e sugestão de sequência didática - Leite, Rondineli Schulthais (2013)
This paper aims to build an effective and systematic learning of the most important geometric concepts of the ninth year of elementary school, using the software GeoGebra as an innovative tool in building a didactic sequence that contributes significantly to the understanding of the geometric content. They are: similarity of triangles, Tales theorem, metric relations in the rectangle-triangle, trigonometry and the Pythagorean theorem. It is hoped that these contents are worked harmoniously, unlike the common practice that organizes these issues on topics as if there was no connection between their concepts. We conducted an investigative research with students and teachers in order to observe the main problems students have in learning geometry in ninth grade, and check possible mistakes made in the teaching and learning process of these geometrical concepts. In possession of the search results, we started the didactic sequence construction, seeking to unclog the main obstacles observed in the leading of these contents, favoring organized learning with teacher's guidance, but constructed by the student. For this, we produced five activities in an introductory aspect, exclusively, of these issues, organized in labor routings so to lead students onto a gradual and consistent learning through manipulations performed in the software GeoGebra. The evaluation of this suggestion of didactic sequence becomes important and deserves further studies to verify how effective it is as a tool in the conducting of teaching these geometric contents.